Facile formulation of sustainable and stable oil-in-dispersion emulsion: A release agent with high demoulding efficacy - Ansar Abbas; Chen Zhang; Guangwei Hu; Sameer Hussain; Ruixia Gao; Jing Li; Yang li; Silong Xu (Chemical Engineering Journal Advances, 2022)
In the hunt of new sustainable release agents for concrete removal with improved demoulding efficacy, oil-in-dispersion (OD) release agents have appeared as favourable emulsions, since they display augmented performance in contrast to conventional oil-in-water (O/W) emulsions. This work presents a novel and facile methodology for sustainable preparation of OD release agent employing emulsifiers as active components to produce stable emulsion, leading to a superior and easier commercial product formulation. The new type of OD release agent is optimized by varying the composition of two food grade emulsifiers named as span-80 and AEO-3 from 2.4 to 7.4% in the formulation. The stability and performance of new OD release agents are studied comprehensively through various parameters like creaming index, viscosity, density, pH tests, water contact angle, droplet size and shape. After dilution five times with water, the OD based release agent containing 5.4–7.4% mixed emulsifier concentrations demonstrate excellent stability even after six months of storage and performed well in physico-chemical lab testing. Moreover, OD release agents showed good application results during on-field industrial trials on iron mould surfaces. The formulated OD release agents on the mould took only 12–15 min to generate a smooth and uniform film that was demoulded easily by sledgehammering about 3–5 times. Thus, easily prepared and highly stable OD release agent could be revolutionary in construction industry for sustainable and rapid removal of mould concrete with high efficacy.